The Church’s Position on the Rule of Clovis (481-511) - abood mohosh, Mohammed; Taher, Prof. Dr. Rabee Haidar (Thi Qar Arts Journal, 2024)
This research highlights the church’s stance on the political developments during the rule of Clovis (481-511 AD). It examines the role of church bishops from the time he assumed power in 481 AD, including their congratulations and guidance on governance, and how they persuaded him to marry a Catholic princess, leading to his conversion to Catholicism. It also discusses the church’s position on his wars against the Germanic kingdoms in Gaul under the pretext of fighting Arianism (500-507 AD), and finally, the church’s role in the Council of Orléans, which organized the administration of Clovis’s kingdom at the end of his reign in 511 AD.After the end of imperial rule in Western Europe in 476 AD by Odoacer and the Germanic tribes, several kingdoms were formed, including the Anglo-Saxons in the English Isles, the Visigothic Kingdom in parts of Gaul and the Iberian Peninsula, and the Merovingian Kingdom of the Franks in Gaul. The Catholic Church had a significant stance on these developments, especially since it was part of the Roman state and under its protection, but it came under the rule of the Germanic tribes.Therefore, the research includes a study of the church’s position on Clovis’s rule as the founder of the Merovingian dynasty. The first section discusses the church’s stance on his assumption of power, marriage, and conversion to Catholicism (481-496 AD). The second section covers the wars Clovis fought against the Germanic kingdoms in Gaul and the church’s position on them. Finally, the third section examines the church’s objectives in supporting a Frankish king, whether pagan or Arian.